Book review - Development psychiatry: Mental health and primary health care in Botswana (1987): by David Ben-Tovim - Flisher, Alan (PINS-Psychology in Society, 2025)
Several recent contributors to this journal (e.g. Freeman, 1988; Shefer, 1988) have highlighted the importance of examining the organisation of health services in other countries in attempting to formulate proposals for the organisation of social services in a post-Apartheid South Africa. This book comprises a worthwhile contribution to this debate. The author attempts to apply what he refers to as his "orthodox British Psychiatric training" during his almost three-year sojourn in Botswana commencing in 1980. His principal responsibility was to co-ordinate the large-scale integration of the previously highly centralised psychiatric services in Botswana with the existing primary health care (PHC) network. During this period the mental health professional complement was at most two psychiatrists, nine psychiatric nursing sisters, one psychiatric social worker who was stationed full-time at the only mental hospital) - and no psychologists whatsoever! Their duty was the provision of mental health services to the population of 930 000, in the second least densely populated country on earth. It is thus quite obvious that if any meaningful impact was to be had it would have to be via the existing PHC services.